Evaluation of enhanced virgin coconut oil and senduduk (Melastoma malabathricum) as anthelmintics against caprine strongyle nematodes - Basripuzi Nurul Hayyan Hassan Basri; Sani, R.A; Ariff, O.M.; Chandrawathani, P. (2013)
A study was conducted to evaluate the anthelmintic properties of enhanced virgin coconut oil (EVCO) and senduduk (Melastoma malabathricum) plant against strongyle nematodes in goats. Two preparations of 10% EVCO dissolved in 90% virgin coconut oil and 10% EVCO dissolved in 90% palm oil, were given orally to two groups of mixed breeds goats. The efficacy test indicated that EVCO was insufficiently active as an anthelmintic. Four concentrations of senduduk solution (1.25, 2.5, 5.0 and 10 mg ml-1) were compared with a control and albendazole in an in vitro test for larvicidal effect. There was no significant larval mortality using senduduk solution. An in vivo test of senduduk was conducted by comparing three groups of goats, namely control, levamisole and treatment groups that were given a daily oral dose of senduduk crude extract with 1g kg-1 from Day 0 to Day 12 and 2 g kg-1 from Day 13 to Day 30. This efficacy test with senduduk also gave negative results. The findings obtained indicated that EVCO and senduduk were ineffective as anthelmintics against caprinestrongyle nematodes at the concentrations used.